A Survey of Leisure Activities that the Elderly Desire (Journal of Advanced Research in Social Sciences, 2020)
The objective of this study was to explore both the indoor and outdoor activities that the elderly desire.  This study employed a questionnaire and in-depth interviews with people aged 50 years and older in Bangkok, Prathum Thani, Samut Pragarn and Phra Nakhon Si Ayutthaya provinces. The sample size was 185. The study showed that the outdoor activities that the elderly preferred were walking in the water, stretching activities and walking. The indoor activities that they preferred were muscle, brain and mind development. The most preferred outdoor activity of the elderly was walking in the water, while their favorite indoor activity was muscle development.